Leading from the emerging future from ego-system to eco-system economies - Scharmer, Claus Otto 1961- (Berrett-Koehler Publishers, Inc., 2013)
Our Time Is NowWe have entered an age of disruption. Financial collapse, climate change, resource depletion, and a growing gap between rich and poor are but a few of the signs. Otto Scharmer and Katrin Kaufer ask, why do we collectively create results nobody wants? Meeting the challenges of this century requires updating our economic logic and operating system from an obsolete "ego-system" focused entirely on the well-being of oneself to an eco-system awareness that emphasizes the well-being of the whole. Filled with real-world examples, this thought-provoking guide presents proven practices f
"A BK Currents Book.". - Includes bibliographical references and index. - Print version record
Keywords: Economics -- Sociological aspects; Social problems -- Economic aspects; Social change -- Economic aspects; Problèmes sociaux; Aspect économique; POLITICAL SCIENCE; Public Policy; Cultural Policy; SOCIAL SCIENCE; Anthropology; Cultural; SOCIAL SCIENCE; Popular Culture; BUSINESS & ECONOMICS; Organizational Behavior; Organizational Behavior; Economics; Sociological aspects; Social change; Economic aspects; Social problems; Economic aspects; BUSINESS & ECONOMICS / General; Economics